A Qualitative Analysis of Information Sharing in Hospice Interdisciplinary Group Meetings. (December 2017) - Washington, Karla T.; Demiris, George; Parker Oliver, Debra; Swarz, Jeffrey A.; Lewis, Alexandria M.; Backonja, Uba
Background: In the United States, hospice agencies are required to convene interdisciplinary group (IDG) meetings no less frequently than every 15 days to review patients' care plans. Challenges associated with information sharing during these meetings can impede efficiency and frustrate attendees. Objectives: We sought to examine information sharing in the context of hospice IDG meetings as a first step toward developing an informatics tool to support interdisciplinary collaboration in this setting. Specifically, we wanted to better understand the purpose of information sharing in IDG meetings and determine the type(s) of information required to fulfill that purpose. Methods, Setting, and Participants: In this qualitative descriptive study, we analyzed video recordings of care plan discussions (n = 57) in hospice IDG meetings and individual interviews of hospice providers (n = 24). Results: Data indicated that sharing physical, psychosocial, and spiritual information is intended to optimize hospice teams' ability to deliver whole-person care that is aligned with patient and family goals and that satisfies regulatory requirements. Conclusion: Information sharing is a key function of hospice teams in IDG meetings. Informatics tools may optimize IDG meeting efficiency by succinctly presenting well-organized and required information that is relevant to all team members. Such tools should highlight patient and family goals and ensure that teams are able to satisfy regulatory requirements.